Development between reality and ambition (Obstacles - vulnerable groups - processors) - جبر الكعبي, صبيح (Al-Adab Journal, 2018)
This study concern with evolution of the concept of development and the improvement of human communities to provide a decent life fill of well-being. In addition, this study focus on the vulnerable group who constitute huge numbers in societies, diagnose obstacles, and treatments. Some proponents agreed that there is no development without planning, the physical side of culture progresses faster than moral side that leads to serious problems furthermore, the difficulty of plan evaluation, and it is necessary to construct industrial base commence from inside not that one which come from outside after liberation from colonialism in all its forms.